Analisis Metode Pembelajaran Tahfidz Dalam Meningkatkan Motivasi Menghafal Al-Qur’an - Hari, Zulma; Rusydi, Rusydi; Misra, Misra (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
The aim of this research is to analyze the importance of motivation in Al-Qur'an tahfidz learning activities, the appropriate methods used by tahfidz supervisors in learning Al-Qur'an tahfidz and the strategies of tahfidz supervisors in providing motivation and using appropriate methods in learning Al-Qur'an tahfidz 'an 'a. This type of research is field research (field research) which is qualitative in nature. Research that uses information obtained from research targets is called respondents and informants through observation, interviews and so on. Primary data sources were obtained from structured interviews and field observations with informants. The resource persons for this research were the School Principal, tahfidz supervisor, and tahfidz participants. Data validity techniques include: Credibility, transferability, dependability and confirmability. The results of this research analysis are that internal motivation can grow because of external motivation such as the method used. Some of the methods used are the talaqqi method, muraja'ah method, wahdah method, sima'i method, takriri method, tasmi' method. Strategy in using methods by developing appropriate method mechanisms in learning.